2007
DOI: 10.1038/sj.jid.5700819
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the IL-1β-Processing Inflammasome Is Involved in Contact Hypersensitivity

Abstract: The inflammasome is a cytosolic protein complex regulating the activation of caspase-1, which cleaves the pro-inflammatory cytokines IL-1beta and IL-18 into their active form. The inflammasome is composed of a NACHT-, LRR- and pyrin (NALP) family member that acts as a sensor for danger signals and the adaptor protein apoptosis-associated speck-like protein containing a CARD domain (ASC), which allows the recruitment of caspase-1 in the complex. In the skin, exposure to contact sensitizers (CS) such as trinitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
335
2
10

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 369 publications
(362 citation statements)
references
References 42 publications
15
335
2
10
Order By: Relevance
“…The principle function of the inflammasome is the cleavage, by the protease, caspase-1, of precursor interleukin molecules into the forms, IL-1b and IL-18 and the subsequent release of these proinflammatory cytokines into the extracellular space (Watanabe et al, 2007). This process involves three steps: firstly, synthesis of precursor molecules, e.g.…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
“…The principle function of the inflammasome is the cleavage, by the protease, caspase-1, of precursor interleukin molecules into the forms, IL-1b and IL-18 and the subsequent release of these proinflammatory cytokines into the extracellular space (Watanabe et al, 2007). This process involves three steps: firstly, synthesis of precursor molecules, e.g.…”
Section: The Role Of P2x Receptors In Neuroinflammationmentioning
confidence: 99%
“…We have recently reported that Hcys can activate NALP3 inflammasomes in podocytes, an intracellular molecular switch of inflammation (33). Inflammasome activation has also been implicated in a number of inflammatory and metabolic diseases, including obesity, gout, hypersensitivity, silicosis, and diabetes, where inhibition of the inflammasome proteins NALP3, ASC, or caspase-1 significantly attenuates the downstream inflammatory reaction produced under these conditions (3,17,26,36). Similarly, our report showed that inhibition of either ASC or caspase-1 could prevent podocyte and glomerular damage induced by hHcys, improving renal structural and functional integrity (33), suggesting an important role for inflammasome activation in mediating the deleterious effects of hHcys.…”
Section: Nadph Oxidase and Inflammasome Activation In Podocytesmentioning
confidence: 99%
“…[18][19][20] Furthermore, 'danger-associated molecular patterns or DAMPs' (non-microbial/pathogenic) such as ATP, imidazoquinoline, monosodium urate crystals (MSU) and the skin irritant trinitrochlorobenzene have been shown to induce NALP3 inflammasome activity. 16,19,[21][22][23] Similar to NALP3, the NALP1 inflammasome can be activated by MDP. 5,15 Moreover, in mice activation of caspase-1 by lethal toxin of B. anthracis is dependent on a functional NALP1b.…”
mentioning
confidence: 99%